Chile’s Green State accreditation program and environmental education: anevaluation from the perspective of public officials - Rungruangsakorn, Carlos (2024)
[Introduction]: The Estado Verde accreditation program is an instrument created by the Chilean Ministry of the Environment so that Chilean public institutions, on a voluntary basis, can conduct environmental management in their facilities. Among the main purposes of the program, it seeks to encourage the advance of environmental habits in public officials through environmental education. [Objective]: To determine if the educational and communicational campaigns promoted by the program have generated changes in the environmental habits and behaviors of civil servants. [Methodology]: The combined method was used, and for this purpose a survey was designed, on a universe of 25 000 employees obtaining a sample of 270 cases, with a confidence level of 90 % and an error level of 5 %. In addition, 15 in-depth interviews were conducted. The results were analyzed separately and then a cross analysis was developed. [Results]: Officials recognize changes in habits favorable to environmental care in their institutions, although these are not generalized. [Conclusions]: While the Green State accreditation program does induce changes in habits and behaviors among public employees, it requires additional reinforcement in the promotion of its educational strategies and modifications in certain requirements to fully achieve its goal in non-formal environmental education. Furthermore, the findings may be useful for Latin American States to adopt pro-environmental actions in the administrative functioning of their public institutions..